Collection of Rice Tungro-Infected Plants from Hotspots in the Philippines - Caguiat, Xavier Greg; Waing, Frodie (International Journal For Research In Agricultural And Food Science, 2018)
Tungro is one of the major rice pests causing as much 100% yield loss when unaddressed. Due to the onset of climate change and reports of breakdown of resistance, a study was designed to collect plants infected by tungro in selected tungro hotspots in the Philippines. Collection of tungro-infected plants were conducted in nine provinces: Isabela, Nueva Ecija, Laguna, Albay, Camarines Sur, Camarines Norte, Negros Occidental, Bukidnon, and North Cotabato. A total of 400 suspected RTD-plants were collected. A total of 311 nucleic acid sequences (201 RTBV and 110 RTSV) were obtained and BLAST data yielded 83% to 100% identity with existing databases. Some sequences matched with RTBV strain RTBV-Ic, complete genome, RTBV isolate TB P194 gene, partial cds and some foreign isolates. Most of the samples were collected in Luzon while Mindanao had the least number of samples in terms of collected tungro-infected plants and the RNA extracted since it is highly dependent on the freshness of the plants. In the long run, knowledge on the genetic variation present in these organisms will help in disease management and development of rice tungro disease-resistant varieties.